Training centers vs. Private coaching - McDill, K. (The Professional Skater PS Magazine, 2008)
While there are hundreds of ice rinks in the US that serve as the training facility for world-class skaters, there are a half dozen facilities that are deemed "training centres", and all of the skaters that work out there are either world class or national class stature. The answer to the question "which is better?" depends on who you are, who you would like to become, what you want and how much you want it - do you want to be in the big production, or do you want to be in the unique situation, handy-crafting skaters one at time?